Past and present distribution and hosts of Longidorus (Nematoda: Dorylaimida) in mainland China - Guo, Kai; Shi, Hongli; Liu, Kun; Zheng, Jingwu (Zootaxa, 2011)
The geographical distribution and host associations of Longidorus in mainland China were determined from a comprehensive survey. Among 2,103 soil samples collected from 12 provinces of China during 2008–2010, nine Longidorus species were identified based on morphological characters: L. henanus Xu & Cheng 1992; L. litchii Xu & Cheng 1992; L. hangzhouensis Zheng et al. 2001; L. pisi Edward, Misra & Singh 1964; L. macromucronatus Siddiqi 1962; L. fangi Xu & Cheng 1991; L. camelliae Zheng et al. 2000; L. jonesi Siddiqi 1962; and L. fursti Heyns et al. 1987. In this study, we compile new data on the distribution and hosts of Longidorus in China and the available historical records reported from China. Longidorus henanus has the most widespread distribution in China, while L. litchii is found only in Fujian province, and L. pisi is recorded for the first time in China. The hosts of the genus Longidorus in mainland China included 39 known and 3 unknown plant genera, all of which are perennial woody plants. No records were from cultivated annual crops.